Perceptions of sexual assault perpetrators, victims, and event depend on system justification beliefs and perpetrator atonement. - Brianna C Delker; Kira K Means; Allison Schwam; Aubrie L Patterson; Camille A Fogel; Amelita Brown; Alex M Czopp; Kate C McLean (PLoS ONE)
When accused of wrongdoing, a sexual assault perpetrator may express atonement, i.e., he may acknowledge harm done, take responsibility, and make amends. Anecdotal observations suggest that mainstream U.S. audiences respond favorably when high-status perpetrators express less atonement, such as telling stories that minimize harm, or place responsibility on the victim. However, empirically, little is known about how perpetrator status and atonement influence audience responses. Informed by system justification theory, this vignette-based experiment tested the hypothesis that the more audiences are psychologically invested in an unequal status quo (i.e., the greater their system justification beliefs), the more they will favor perpetrators (vs. victims), especially when high-status perpetrators atone less, and low-status perpetrators atone more. In a pre-registered 2(perpetrator status: low, high) x 3(perpetrator narrative atonement: low, medium, high) x continuous(participant system justification) between-subjects design, U.S. adults (N = 895) were randomly assigned to read 1 of 6 first-person stories by a white male who has been accused of sexual assault by a female acquaintance. Dependent measures included perceived severity of and relative responsibility for the assault, empathy toward perpetrator and victim, and ratings of their likeability and positive personality traits. Hierarchical regression analysis revealed that, instead of the hypothesized interactive effects, there were consistent main effects of system justification and atonement across perpetrator status levels. The greater their system justification beliefs, the more participants favored perpetrators, the less severe they rated the assault, and the less they favored victims. Greater perpetrator atonement boosted favorability ratings for him and the victim. Conversely, less perpetrator atonement diminished his favorability ratings, but also made the assault appear less severe and less his (vs. the victim's) responsibility. Findings underscore the strong influences that perpetrator stories and psychological investment in an unequal status quo have on perceptions of sexual violence.